Hayrabolu Irrigation Scheme Information System - Erguven, G. O.; Sener, M. (UNIV NAMIK KEMAL, 2012)
GIS (Geographical Information System) is a effective tool that support irrigation management for decision makers and it generally works in cooperation with graphical and ungraphical data. In context of this study, GIS database belonged to Hayrabolu Irrigation Scheme waspurposed for helping irrigation management. Parcel, irrigation channeland drainage channel layers were created in thisdatabase. The parcel data contains location place, parcel number, crop information were entered in parcel layers. Also irrigation data (channel name, channel type, irrigation area, channel flows) and drainage data (channel name, channel length) are entered in channel an d drainage layer respectively. This database ensure us that different analysis opportunity with query and analysis features of ArcGIS Desktop software and option for getting output in type of maps and tableswith analysis result. This type databases are designed for helping take more right decision and they get attention from different users like researchers and managers by reason of their strong feature is about collecting numerous information in different type format.
Keywords: Irrigation Scheme; Database; Geographical Information System; ArcGIS; Agriculture